Evaluation towards internship program of vocational school students in automotive engineering - Sulasdi Sulasdi; Bambang Noor Achsan; Fatwa Tentama (Universitas Ahmad Dahlan, 2020)
The purpose of this evaluation research is to evaluate the implementation of the job training (internship) program at SMK Negeri Nusawungu, Cilacap, in automotive light vehicle engineering expertise in 2018/2019. The evaluation used the Context, Input, Process, Product (CIPP) model. This research involved the object of research of the implementation of internship program which is carried out at the SMK N Nusawungu Cilacap in automotive light vehicle engineering expertise in 2018/2019. The data source in this study is the fieldwork practices and students in automotive light vehicle engineering expertise competencies who have implemented internship in the academic year 2018/2019. Students who were respondents were taken with a proportionate random sampling technique, the evaluation model used was the CIPP evaluation model with qualitative evaluation methods. Data collection was taken through questionnaires, interviews, and documentation. Data analysis uses descriptive statistics. The results suggest that the internship program was well run.